(untitled) (American Journal of Islam and Society, 1985)
The ideological and political history of Pakistan is marked by a continuing debate on the nature of the Islamic political system and its concrete manifestation in the constitutional framework of the state. Even the Objectives Resolution which was adopted in 1949 and was hailed by the religious political groups as a “landmark” in the history of Islamic constitutional thought could not bring about a broad consensus among the politically relevant sectors of society. The three subsequent constitutions adopted in 1956,1962, and 1973 have also failed to resolve the controversies over the nature, characteristics, functions, and structure of an Islamic state. The problem assumed new significance after the present martial law regime of General Mohammad Zia-ul-Haq initiated the process of Islamization, postponed the scheduled general elections and extended its tenure for an indefinite period. These moves were preceded by President Zia-ul-Haq-s expressing his aversion for the Western democratic system and its institutions (i.e., parliament, parties, elections, etc.). He felt that there was no scope for such divisive institutions in an Islamic polity and that he would introduce an alternative political system based on truly Islamic principles. He gave no details of what he actually meant by a “true Islamic polity”, but it was apparent from his statements and actions that this “true Islamic polity” was anything but what is generally recognized as democratic. This polity, moreover, was not necessarily founded on the principle of majority rule. It was quite possible-and indeed legitimabin this system for an individual or a group to continue ruling the country against the wishes of the majority of the people. President Zia asserted that according to Islam only “right decisions” were to be respected and, if the majority were“misguided”, its verdict would have to be ignored. Addressing a public meeting in Islamabad in 1983, for example, President Zia said: ...